Maturity assessment of tomato fruit based on electrical impedance spectroscopy - Li, Jinyang; Xu, Yao; Zhu, Wenjing; Wei, Xinhua; Sun, Hongwei (International Journal of Agricultural and Biological Engineering, 2019)
Ripening is important to tomato quality, taste and nutrition. In this study, the maturity of plant-fruit was on-line investigated based on electrical impedance spectroscopy (EIS). The electrodes with sensing unit for contact force between samples and electrodes were designed. After fruits turn into green-white, impedance measurements were conducted on the fruit samples at various ripening stages in the range of 1 Hz to 1 MHz. The optimal frequencies (100 Hz, 1 kHz and 1 MHz) for maturity assessment were selected and five electrical impedance parameters at three sensitive frequencies were determined. The equivalent circuit model with CPE was developed and the model performance was evaluated. The soluble solid content and pH of fruit were determined and analyzed to explain the variations in EIS parameters sufficiently. Results showed that the impedance, phase angle, resistance, reactance and capacitance increased with the progression of maturity. The selected impedance parameters could be used to classify tomato samples into immature class or mature class with the accuracy of 88.3%. Impedance analysis for different samples from the same branch demonstrated that the ripening stage of all other samples could be predicted and assessed by the impedance spectroscopy from one sample. Keywords: tomato fruit, maturity, discriminate analysis, electrical impedance spectroscopy DOI: 10.25165/j.ijabe.20191204.4664 Citation: Li J Y, Xu Y, Zhu W J, Wei X H, Sun H W. Maturity assessment of tomato fruit based on electrical impedance spectroscopy. Int J Agric & Biol Eng, 2019; 12(4): 154–161.